2021
DOI: 10.1186/s12967-021-02870-x
|View full text |Cite
|
Sign up to set email alerts
|

High copy number variations, particular transcription factors, and low immunity contribute to the stemness of prostate cancer cells

Abstract: Background Tumor metastasis is the main cause of death of cancer patients, and cancer stem cells (CSCs) is the basis of tumor metastasis. However, systematic analysis of the stemness of prostate cancer cells is still not abundant. In this study, we explore the effective factors related to the stemness of prostate cancer cells by comprehensively mining the multi-omics data from TCGA database. Methods Based on the prostate cancer transcriptome data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…It is widely accepted that replication stress plays a key role in initiating anti-tumor immunity by inducing cancer-related neoantigens ( 31 , 32 ), and its absence is intensively correlated with the immune desert phenotype. Consequently, the low immunity and high level of CNV can jointly contribute to strong cancer stemness ( 33 ), accounting for the result that patients of CS3 were tolerant of many ATR and week1 inhibitors in our study.…”
Section: Discussionmentioning
confidence: 67%
“…It is widely accepted that replication stress plays a key role in initiating anti-tumor immunity by inducing cancer-related neoantigens ( 31 , 32 ), and its absence is intensively correlated with the immune desert phenotype. Consequently, the low immunity and high level of CNV can jointly contribute to strong cancer stemness ( 33 ), accounting for the result that patients of CS3 were tolerant of many ATR and week1 inhibitors in our study.…”
Section: Discussionmentioning
confidence: 67%
“…Chen et al found that only an inflection point was observed in a few PCa samples, which can separate putative malignant cells from non-malignant cells in PCa. However, this distinction was not so precise in other samples [ 17 ], which may be because some localized PCa tumors have been shown to have a silent genome [ 20 ]. Furthermore, previous DNA sequencing studies have revealed that 0–50% of PCa genomes have CNAs and that CNAs are also a prognostic factor for PCa [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the high expression of this gene may cause breast cancer patients to have no immune response to the PD-1 antibody, which may be a prognostic marker of the PD-1 antibody. In addition, the copy number variation of the gene is also related to the infiltrating immune cells in the tumor tissue (37). There are fewer infiltrating immune cells in the tumor tissue with increased or decreased copy number, indicating that the copy number variation of the gene may affect the immune cell infiltration, which needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%